Sol-Gel Synthesis of Some Rare Earth Cuprates RE2CuO4, (RE = La, Eu and Nd). - A. SHERIEF., MARWA (Asian Journal of Chemistry, 2010)
Two samples of rare earth cuprates, RE2CuO4 (RE =La, Eu, Nd) were prepared by using sol-gel method. The first sample was prepared by mixing RECl3 and CuCl2 with molar ratio 1:1 in presence of ethylene oxide gas as gelating agent. The product was dried at 120 °C. The second one was prepared from RECl3 and CuCl2 and using citric acid and ethylene glycol for gelation with molar ratio 1:1:10:40. The product was dried at 130 °C to give a gel form of RE2CuO4. The gel was converted to powder by heating at 350 °C. The produced samples were characterized by XRD, IR, thermal analysis and SEM. The results indicate that RE2CuO4 in a very fine particle size was formed. The analysis of XRD pattern showed that a single phase of RE2CuO4 was formed by using the first method while a residual of the precursor material was appeared on using the second method. The electrical conductivity (O' ) of the produced samples were measured between 25-300 °C after sintering at 850 °C for 2 h. The results of measurements indicate that all the produced samples behave as semiconductor materials where the value of electrical conductivity (O' ) increased with temperature.